Weathered microplastics in human blood: unraveling the effect of structural changes at the particle surface on coagulation and platelet activation - Manfred F. Maitz; Robin Lenz; Steven Winkler; Mara F. Abschke; Carsten Werner; Dieter Fischer (Microplastics and Nanoplastics)
Abstract Background Microplastics (MPs) from environmental sources have been detected in various human organs, including the circulatory system. The biological response to such MPs is usually tested under artificial conditions, restricting their relevance. Objectives Probing the influence of MPs with realistic properties concerning size, shape, weathering-induced polymer degradation, and concentration on the response of human whole blood. Methods This study examines the response of human whole blood to NPs of different cryomilled commodity polymers at a concentration range of 4 – 100 µg/ml, and mean size of about 25 µm, covering microplastic concentrations and size reported for organs and blood. Environmental degradation of the polymers was simulated through graded artificial weathering of the particles for 14 days in cyclic UV, temperature, and humidity changes, representing about 1.5 years of environmental weathering, and analyzed by Raman and Fourier transform infrared (FTIR) spectroscopy, and zeta potential measurement. Results Spectroscopic analysis of the bulk polymers indicated the degradation of aromatic polymers with the formation of carboxylic acid groups. Surface-sensitive zeta potential measurements also demonstrated a shift to more negative values of the polymers with aromatic groups. In contact with whole blood, these structural changes were associated with a pronounced coagulant response to the weathered polymers polystyrene (PS), acrylonitrile butadiene styrene (ABS), polyethylene terephthalate (PET), and polyvinylchloride (PVC) containing aromatic plasticizers, compared to the pristine ones. There was a primary correlation with the changes in surface properties observed in the zeta potential shift. In the case of PET, these surface- and biological effects did exceed the changes in the FTIR and Raman spectra. A dose-dependency to the particle count and the intensity of weathering was observed. Discussion These findings underscore the impact of environmental weathering of common MPs on their biological performance.